Polymer-layered silicate nanocomposites: preparation, properties and uses of a new class of materials - Alexandre, Michael; Dubois, Philippe (Materials science & engineering. R, Reports : a review journal, 2000)
This review aims at reporting on very recent developments in syntheses, properties and (future) applications of polymer-layered silicate nanocomposites. This new type of materials, based on smectite clays usually rendered hydrophobic through ionic exchange of the sodium interlayer cation with an onium cation, may be prepared via various synthetic routes comprising exfoliation adsorption, in situ intercalative polymerization and melt intercalation. The whole range of polymer matrices is covered, i.e. thermoplastics, thermosets and elastomers. Two types of structure may be obtained, namely intercalated nanocomposites where the polymer chains are sandwiched in between silicate layers and exfoliated nanocomposites where the separated, individual silicate layers are more or less uniformly dispersed in the polymer matrix. This new family of materials exhibits enhanced properties at very low filler level, usually inferior to 5 wt.%, such as increased Young’s modulus and storage modulus, increase in thermal stability and gas barrier properties and good flame retardancy.